Rekayasa Nanoselulosa Bakteri sebagai Platform Nano-Biomaterial untuk Terapi Obat dan Antimikroba: Perspektif Pengobatan Modern - Zakia Asrifah Ramly (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2025)
Antimicrobial resistance (AMR) continues to rise globally, diminishing the efficacy of conventional antibiotics and driving the need for advanced biomaterial-based therapeutic strategies. Bacterial nanocellulose (BNC) has emerged as a highly promising platform due to its nanoscale fibrillar structure, high porosity, exceptional purity, and excellent biocompatibility. Its large surface area and hydrogel-like properties enable high drug-loading capacity and controlled release, making BNC an ideal matrix for therapeutic delivery. Functionalization of BNC with metallic nanoparticles (AgNP, ZnO, CuO), antibiotics, plant-derived bioactives (e.g., quercetin, curcumin), and innovative agents such as lytic enzymes or metal–organic frameworks has demonstrated markedly enhanced antibacterial and antibiofilm performance. In vitro studies report broad- spectrum inhibition, biofilm reduction up to 95%, and improved drug stability through sustained release. In vivo evaluations using wound models reveal accelerated healing (30–50%), reduced bacterial burden by up to 4 log CFU, and superior tissue regeneration with minimal systemic toxicity. Despite these promising outcomes, gaps remain regarding long-term safety, nanoparticle–host interactions, and standardized testing protocols. Overall, current evidence highlights BNC as a versatile and potent nanobiomaterial for antimicrobial therapy and drug delivery, although successful clinical translation will require comprehensive in vivo validation and methodological harmonization.